Diagnostic Accuracy of Diffusion Weighted Magnetic Resonance Imaging.docx - Sajida Majeed; Nooshin Akhtar; Komal Qazi; Imran Hussain; Farhan Qureshi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: To determine the diagnostic accuracy of diffusion weighted magnetic resonance imaging in diagnosing urinary bladder carcinoma, taking histopathology as gold standard. Methodology: This study was conducted at Department of Diagnostic Radiology & Department of Urology, Sheikh Zayed Hospital, Rahim Yar Khan from February 2019 to July 2019. A total of 162 patients presenting with hematuria (RBCs >100 on urine complete examination) and presence of irregular soft tissue structure projecting into bladder lumen from a fixed mural site on ultrasonography and age 20-60 years of either gender were included. Patients with operated for urinary bladder cancer, biopsy proven urinary bladder carcinoma and any contraindication to MRI were excluded. All the patients were then undergoing DW-MRI and presence or absence of urinary bladder carcinoma is noted. The DW-MRI findings were correlated with histopathology findings. Results: In DW-MRI positive patients, 74 (True Positive) had urinary bladder cancer and 11 (False Positive) had no urinary bladder cancer on histopathology. Among 77, DW-MRI negative patients, 01 (False Negative) had urinary bladder cancer on histopathology whereas 76 (True Negative) had no urinary bladder cancer on histopathology (p=0.0001). Overall sensitivity, specificity, positive predictive value, negative predictive value and diffusion weighted magnetic resonance imaging in diagnosing urinary bladder carcinoma, taking histopathology as gold standard was 98.67%, 87.36%, 87.06%, 98.70% and 92.59% respectively. Conclusion: This study concluded that DW-MRI is a highly sensitive and accurate non-invasive modality for diagnosing urinary bladder cancer.